Comparison of the Accuracy Levels of Naive Bayes, Random Forest, and Long Short-Term Memory (LSTM) Methods in Predicting Gold Jewelry Sales - Pandu W, Muhammad Arfianto; Saputro, Rujianto Eko; Purwadi, Purwadi; Rohmah, Umdah Aulia (Informatika, Universitas Jenderal Soedirman, 2026)
Gold has long been recognized as a safe haven asset, especially during economic uncertainty. Accurate prediction of gold jewelry sales is essential for inventory management and business strategy, particularly in high-demand regions such as Imogiri. This study aims to compare the accuracy levels of three machine learning methods—Naïve Bayes, Random Forest, and Long Short-Term Memory (LSTM)—in predicting gold jewelry sales using historical transaction data from Toko Emas Parimas. The dataset comprises 4,595 records from January 2022 to December 2024. The research employs data preprocessing, including data cleaning, feature transformation, and normalization, followed by classification into sales categories. Two data-splitting schemes (80:20 and 70:30) were implemented to evaluate model generalization. The models were trained and tested using performance metrics such as accuracy, precision, recall, and F1-score. The results show that Random Forest achieved perfect classification with an accuracy of 1.00 in both schemes, outperforming the other models. Naïve Bayes also performed well with accuracy up to 0.98, while LSTM showed moderate results with accuracy ranging from 0.82 to 0.88. These findings indicate that Random Forest is the most reliable model for sales prediction of gold jewelry, especially for static classification tasks. The study provides practical insights for retailers and decision-makers in selecting suitable analytical models, and it highlights the importance of aligning analytical methods with data characteristics to improve decision support systems in retail.